Text Information Ontological Analysis in the Computer Simulation Systems - Bulgakova, O. (Індуктивне моделювання складних систем, 2014)
The paper proposes an approach for automation ontological analysis of text information using generalized iterative algorithm (GIA) of inductive modeling. The technology for the information collecting and sorting, which includes four phases: input data formalization (extract data from external sources, their transformation and loading in the repository); data analysis (using the GIA inductive modeling); information definition to a specific ontology (ontology instance); new ontologies creation (instances) based on analyzed information.